Venti di guerra nello Spazio (GEOmedia, 2022)
In recent years it has been repeatedly discussed, even on the pages of this Magazine, of the dependence of our society from space systems and attacks, more or less evident, worked against them in various forms.Particularly worrying, for whom deals with geomatics, were the various and often repeated episodes of "jamming" and "spoofing" towards signals GNSS, especially GPS, in various areas of the world, such as the Middle East, Strait of Hormuz, China Sea, Korea. No less serious, though perhaps less well known, the attempts at attacks cybernetic versus satellite systems for Earth observation and the communications.